-16=-(s+-20)

Simple and best practice solution for -16=-(s+-20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=-(s+-20) equation:



-16=-(s+-20)
We move all terms to the left:
-16-(-(s+-20))=0
We add all the numbers together, and all the variables
-(-(s-20))-16=0
We calculate terms in parentheses: -(-(s-20)), so:
-(s-20)
We get rid of parentheses
-s+20
We add all the numbers together, and all the variables
-1s+20
Back to the equation:
-(-1s+20)
We get rid of parentheses
1s-20-16=0
We add all the numbers together, and all the variables
s-36=0
We move all terms containing s to the left, all other terms to the right
s=36

See similar equations:

| 16u-15u+18=3u+14 | | -(w+-50)=-35 | | 7(f-92)=42 | | 2p+3p+8-4=54 | | f(×)=-3+1 | | -13/12=2/3k-13/4 | | 20=7j-15 | | 7(n-77)=63 | | 1/2(3x+6)=36 | | p+p/2=1260 | | 2(7x-10)+19=55 | | 6^3m=20 | | 4x–10=2x+2 | | p+p2=1260 | | 2/3(3x−5)=3 | | -6+m-4=-17 | | 17x–7x=x+18 | | (x-1)^2-4=44 | | 6+5.25x=30+4.5x | | x+3x+3x+4x+4x+5x=360 | | (4x+8)/2=18 | | (12x+15)+(6x-27)+105+75=180 | | (x+9)/4=10 | | 4t-12=6(t=3) | | 3x²+2x-33=0 | | (2x+1)+39=190 | | 5n+7=81 | | (p+3)(p+10)=0 | | 15x+12+3x(2x-6)=3x-(21x-1)+2 | | X-50+x+x-70=180 | | X²-7x=20 | | 2.14x-12.18=-576 |

Equations solver categories